Current situation in teaching and learning English listening at Tay Ho High School in Hanoi and solutions. - Nguyen, Thi Phuong Quynh (University of Languages and International Studies, 2017)
It is undeniable that English has become more and more important in any society. Being aware of this important of English as well as the necessity of developing the learners’ communicative competence, the new text book has been applied with some considerable...